Impacts of land use changes on water conservation in the Songhuajiang River basin in Northeast China using the SWAT model - Beibei Ding; Yuqian Li; Gary W. Marek; Jianing Ge; Yiwen Han; Kelin Hu; Tiezhu Yan; Srinivasulu Ale; Guilong Zhang; Raghavan Srinivasan; Yong Chen (Agricultural Water Management)
The Songhuajiang River basin (SRB) in Northeast China underwent obvious changes in land use in recent years, which might lead to intense changes in basin hydrology and water conservation. Therefore, to evaluate the effects of land use changes on the hydrological cycle and associated water conservation in the SRB, a calibrated Soil and Water Assessment Tool (SWAT) model was used. The model auto-calibration was conducted using the SWAT-CUP (SWAT Calibration and Uncertainty Procedures) tool. Results revealed that calibration of three crop yields of corn (Zea mays L.), rice (Oryza sativa L.), and soybean (Glycine max L.) during the study period (2001–2018) had the Percent BIAS (PBIAS) values of −8.7 %∼3.0 %, 6.2 %∼19.7 %, and −8.7 %∼7.2 %, respectively in 15 zones. Good agreements were obtained for simulated results of streamflow in comparison with measured data from 12 hydrological stations, in which the overall Nash-Sutcliffe Efficiency (NSE) values for the calibration (2009–2012) and validation (2013–2015) periods were 0.60 and 0.64, respectively, and the overall PBIAS values were 7.7 % and 15.4 %. For the land use changes, the hydrological cycle of corn to rice (all hydrological variables change by more than 18 %) was more complex and intense than that of corn to soybean (all hydrological variables change not exceed 5 %). According to the simulation results of water conservation, this study found that the implementation of the policy-driven replacement of corn with soybean in the SRB was feasible. As for the economy-driven conversion from corn to rice, it is necessary to consider the substantial impacts on the hydrological cycle and the decline in water conservation. Based on simulation results, it is not recommended that producers in the Western SRB promote corn to rice conversion.